2015
DOI: 10.3758/s13428-015-0571-6
|View full text |Cite
|
Sign up to set email alerts
|

The concurrent use of three implicit measures (eye movements, pupillometry, and event-related potentials) to assess receptive vocabulary knowledge in normal adults

Abstract: Recent years have seen the advent and proliferation of the use of implicit techniques to study learning and cognition. One such application is the use of event-related potentials (ERPs) to assess receptive vocabulary knowledge. Other implicit assessment techniques that may be well-suited to other testing situations or to use with varied participant groups have not been used as widely to study receptive vocabulary knowledge. We sought to develop additional implicit techniques to study receptive vocabulary knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 59 publications
6
24
0
Order By: Relevance
“…Overall, Ledoux et al (2016) demonstrated that all three measures showed effects that are consistent with prior work using EMs, PD, and ERPs as implicit measures of language, indicating that they can be used together to assess receptive vocabulary in TD adults. Critically, although the participants made behavioral responses throughout the tasks, all three implicit measures demonstrated the participants’ ability to distinguish between ‘known’ and ‘unknown’ words without relying on behavioral responses.…”
Section: Implicit Measures Of Receptive Vocabularysupporting
confidence: 80%
See 2 more Smart Citations
“…Overall, Ledoux et al (2016) demonstrated that all three measures showed effects that are consistent with prior work using EMs, PD, and ERPs as implicit measures of language, indicating that they can be used together to assess receptive vocabulary in TD adults. Critically, although the participants made behavioral responses throughout the tasks, all three implicit measures demonstrated the participants’ ability to distinguish between ‘known’ and ‘unknown’ words without relying on behavioral responses.…”
Section: Implicit Measures Of Receptive Vocabularysupporting
confidence: 80%
“…We have previously demonstrated the complementary use of EMs, PD, and ERPs as implicit measures of receptive vocabulary knowledge in TD adults using high-frequency ‘known’ words (eg, airplane ) and low-frequency ‘unknown’ words (eg, cherimoya) (Ledoux et al, 2016). In a visual world paradigm, during which EM and PD data were collected, four pictures were followed by a spoken word matching one of the pictures.…”
Section: Implicit Measures Of Receptive Vocabularymentioning
confidence: 99%
See 1 more Smart Citation
“…One limitation of this paradigm is that it can only be used with individuals who are familiar with the words or pictures being presented. Prior work has shown that N400 effects do not occur if the lexical item is outside the individual's vocabulary range 32,35 . Therefore it is important that participants either have average to above-average verbal and reading abilities, or that care is taken to ensure that all stimuli used in the experiment fall within the vocabulary range of the individual.…”
Section: Discussionmentioning
confidence: 99%
“…Recent progress in social cognitive neuroscience (SCN), a field of study including biological processes and cognitionbased aspects (Lieberman, 2010), is confuting the majority of social cognition models that suggest that humans can analyze and correctly verbalize their beliefs, feelings, and behaviors (Nosek et al, 2011), showing that our social interactions are mostly governed by unconscious processes that happen without conscious awareness or control (Forscher et al, 2019). To study the unconscious processes, several implicit measures, including brain images, behavior, and psychophysiological tracking, have been developed as alternative research methods to explicit measures since they are able to capture implied brain processes (Ledoux et al, 2016).…”
Section: Implicit Processes As Pillars For Asd Biomarkersmentioning
confidence: 99%